How to inflect uninflected words in Lithuanian - Petit, Daniel (Baltistica, 2025)
In Lithuanian, there are a number of quantificational adverbs that can perform the same functions as noun forms, even though they are invariable and are not marked by case endings, e.g. daũg ‘much’, mãža / mažaĩ ‘little, few’, ganà ‘enough’, kíek ‘how much’, tíek ‘so much’. The purpose of this article is to determine what strategies the Lithuanian language uses to compensate for the lack of case marking in these forms and to prevent this from leading to ambiguity about their syntactic function. The data from the Old Lithuanian texts are particularly interesting because they show a variety of possibilities: (1) the use of derived variants with case marking (daũgelis ‘much’, daugýbė, daugùmas ‘great number’), (2) the use of inflected forms (*daugis, *kiekas, *tiekas), (3) the transfer of the inflectional markers to the noun accompanying these adverbs (e.g. daũg žmonė́ms dative plural). These different possibilities obey both the organic logic of the language itself and sometimes linguistic interference in the case of translated texts.
Keywords: adverb; case; quantifier; Old Lithuanian